Efficacy of Quilting Sutures and Fibrin Sealant Together for Prevention of Seroma in Extended Latissimus Dorsi Flap Donor Sites - In Soo Shin (Archives of Plastic Surgery, 2012)
BackgroundThe extended latissimus dorsi flap is important for breast reconstruction. Unfortunately, donor site seroma is the most common complication of extended latissimus dorsi flap for breast reconstruction. Although using fibrin sealant in the donor site reduces the rate of seroma formation, donor site seroma remains a troublesome complication. The purpose of this study was to analyze the effectiveness of the combination of quilting sutures and fibrin sealant in the latissimus dorsi donor site for the prevention of seroma.MethodsForty-six patients who underwent breast reconstruction with extended latissimus flap were enrolled in the study. The patients received either fibrin sealant (group 1, n=25) or a combination of fibrin sealant and quilting sutures (group 2, n=21) in the extended latissimus dorsi donor site. Outcome measures were obtained from the incidence, volume of postoperative seroma, total drainage amount, indwelling period of drainage, and duration of hospital stay.ResultsThe incidence of seroma was 76% in group 1 and 42.9% in group 2 (P=0.022). We also found significant reductions in seroma volume (P=0.043), total drainage amount (P=0.002), indwelling period of drainage (P=0.01), and frequency of aspiration (P=0.043). The quilting sutures did not affect the rate of drainage, tube reinsertion, or hospital stay.ConclusionsThe use of quilting sutures combined with fibrin sealant on the latissimus dorsi flap donor site is helpful for reducing the overall seroma volume, frequency of aspiration, and total drainage amount.